The Important Role of Equivalence Scales: Household Size, Composition, and Poverty Dynamics in Russia - Kseniya Abanokova; Hai-Anh Dang; Michael Lokshin (Institute of Labor Economics (IZA), 2020)
Hardly any literature exists on the relationship between equivalence scales and poverty dynamics for transitional countries. We offer a new study on the impacts of equivalence scale adjustments on poverty dynamics for Russia, using the equivalence scales constructed from subjective wealth and more than 20 waves of household panel survey data from the Russia Longitudinal Monitoring Survey. Our analysis suggests that the equivalence scale elasticity is sensitive to household demographic composition. The adjustments for the equivalence of scales result in lower estimates of poverty lines. We decompose poverty into chronic and transient components and find that chronic poverty is positively related to the adult scale parameter. Chronic poverty, however, is less sensitive to the child scale factor compared to the adult scale factor. Interestingly, the direction of income mobility might change depending on the specific scale parameters that are employed. Our results are robust to different measures of chronic poverty, income expectations, reference groups, functional forms, and various other specifications.
Keywords: I30; J10; O15; 330; poverty; poverty dynamics; equivalence scale; Russia; panel survey